2013
DOI: 10.1007/s10856-013-5074-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of zirconium and titanium implants in rat: osseointegration and bone material quality

Abstract: Permanent metal implants are widely used in human medical treatments and orthopedics, for example as hip joint replacements. They are commonly made of titanium alloys and beyond the optimization of this established material, it is also essential to explore alternative implant materials in view of improved osseointegration. The aim of our study was to characterize the implant performance of zirconium in comparison to titanium implants. Zirconium implants have been characterized in a previous study concerning ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
4
28
0
1
Order By: Relevance
“…Accordingly, in EIS spectra the increase of total impedance modulus together with a rise in the phase angle plot in the low frequency region, and a shift to higher frequencies that can be related to the increase of the barrier effect for the anodised condition. This fact has already been observed in previous studies conducted on plane zirconium samples where the stability of the oxide is formed and the thickness increase for the anodised samples were demonstrated (Hoerth et al 2014). …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Accordingly, in EIS spectra the increase of total impedance modulus together with a rise in the phase angle plot in the low frequency region, and a shift to higher frequencies that can be related to the increase of the barrier effect for the anodised condition. This fact has already been observed in previous studies conducted on plane zirconium samples where the stability of the oxide is formed and the thickness increase for the anodised samples were demonstrated (Hoerth et al 2014). …”
Section: Discussionsupporting
confidence: 78%
“…Surface modification of zirconium by anodization has proved to be a treatment that can keep corrosion parameters in low values in simulated body fluid while being able to promote Ca–P compounds’ precipitation on the surface endorsing the bioactivity of the material and promoting bone regeneration in vitro (Gomez Sanchez et al 2013). The preliminary in vivo test demonstrated that although no Ca–P compounds were detected in the Zr with the native oxide, new bone was developed as in the anodized Zr, Although osseointegration was observed for anodized and non-anodized samples, the quality, kinetics of growing and maturity are not well established (Gomez Sanchez et al 2013; Hoerth et al 2014). Since the primary interaction between the tissue and the implant in through the surface, the understanding of their interaction for long-term service deserves further research.…”
Section: Introductionmentioning
confidence: 99%
“…The osseointegration and quality of bone have previously been discussed in an in-vivo study of rats in which the newly formed bone around Zr implants was found to be at least equal, in terms of the quality and the compositional and structural properties of the bone, compared with that of Ti implants [50]. The quantification of the mineral-to-matrix ratio revealed a higher degree for the newly formed bone around the Zr implants as compared with the Ti implants, in line with the observations made in the present study, which might explain the improved stability.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study evaluating the osseointegration of zirconium and titanium implants in rat, a high degree of mature bone was observed around both materials, showing the potential of zirconium as an implant material per se. Further, the newly formed bone tissue surrounding the zirconium implant had a higher mineral-to-matrix ratio [35]. It has been shown that the mineralto-matrix ratio in bone is an important parameter with regard to the mechanical properties and their capacity to distribute the strain [36].…”
Section: Discussionmentioning
confidence: 99%